Concurrent metaphylaxis with aureomycin and Draxxin in high-risk calves has no additive effects on cattle health and performance - J.O. Wallace; Christopher D. Reinhardt; Daniel U. Thomson (Kansas Agricultural Experiment Station Research Reports, 2009)
The shipping and receiving period is one of the most stressful experiences during a calf's lifetime. Stressors include weaning, commingling, transportation, processing, feed and water changes, and disease challenge placed on the animal upon entering a stocker operation or feedlot. These stressors result in decreased appetite, loss of body mass, decreased immunity, and increased risk of disease. Bovine respiratory disease complex has one of the highest treatment costs of all diseases affecting feedlot cattle and can negatively affect feedlot performance and carcass characteristics of animals, resulting in decreased profit. Mass medication (metaphylaxis) is the treatment of all cattle at arrival processing despite observed health status by using either injectable or feed-grade antibiotics. However, no research has examined effects of concurrent metaphylaxis with both Draxxin (Pfizer Animal Health; New York, NY) and chlortetracycline simultaneously. Therefore, the objective of this study was to examine effects of concurrent metaphylaxis with Draxxin and chlortetracycline upon arrival on high-risk stocker calf health and performance.
Keywords: Cattlemen& #x27; s Day; 2009; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1010; Kansas Agricultural Experiment Station contribution; no. 09-168-S; Beef; Cattle; Draxxin; Weaning